2019
DOI: 10.7717/peerj.7726
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and molecular characterization of the indigenous Staphylococcus aureus strain K1 with the ability to reduce hexavalent chromium for its application in bioremediation of metal-contaminated sites

Abstract: Background Urbanization and industrialization are the main anthropogenic activities that are adding toxic heavy metals to the environment. Among these, chromium (in hexavalent: Cr+6 and/or trivalent Cr+3) is being released abundantly in wastewater due to its uses in different industrial processes. It becomes highly mutagenic and carcinogenic once it enters the cell through sulfate uptake pathways after interacting with cellular proteins and nucleic acids. However, Cr+6 can be bio-converted into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 56 publications
1
13
0
Order By: Relevance
“…Chromium removal in water by P. aeruginosa has been reported extensively [ 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 ], but to the best of our knowledge, no reports are found in the literature that use electrospun fibers as promoters of intended P. aeruginosa biofilm formation for the removal of chromium from water, and thus a comparison between the reported bioremediation potential of P. aeruginosa biofilms created with non-nanostructured substrates and our results is listed in Table 5 , in order to see the difference in the removal capacity with and without the use of nanostructured substrates.…”
Section: Discussionmentioning
confidence: 99%
“…Chromium removal in water by P. aeruginosa has been reported extensively [ 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 ], but to the best of our knowledge, no reports are found in the literature that use electrospun fibers as promoters of intended P. aeruginosa biofilm formation for the removal of chromium from water, and thus a comparison between the reported bioremediation potential of P. aeruginosa biofilms created with non-nanostructured substrates and our results is listed in Table 5 , in order to see the difference in the removal capacity with and without the use of nanostructured substrates.…”
Section: Discussionmentioning
confidence: 99%
“…Zou et al (2014) analyzed metal-contaminated locals and reported the ability of S. aureus to resist and reduce chromium (VI) to chromium (III) and adsorb uranium (VI). Tariq et al (2019) confirmed through biochemical and phylogenetic analyses that the S. aureus K1 strain is promising and can remove chromium from metal-polluted environments. Furthermore, biofilms produced by S. aureus -one of the structures responsible for the bacterium's pathogenicity, have been tested for uranium bioremediation ability (SHUKLA et al, 2020).…”
Section: Resultsmentioning
confidence: 69%
“…ese results are very important to show not only their importance in biodegradation but also to avoid any contamination of the soil with these pathogenic bacteria. Bioremediation of polluted oily sludge employing pathogenic bacteria including Pseudomonas aeruginosa, B. cereus, Staphylococcus sp., has been demonstrated [36,46,47]. Here, we showed the evidence that Bacillus could be the bright choice for bioremediation since strains are deeply considered like GRAS (generally recognized as safe) organisms.…”
Section: Discussionmentioning
confidence: 70%